The Rainbow Connection: Theorizing the Efficacy of Private Texts - Liz Rohan (Journal of the Assembly for Expanded Perspectives on Learning, 2012)
Texts written privately often find new contexts, new uses, if writers become mindful of Bakhtin’s notion of “great time.”